gp91phox, a Novel Biomarker Evaluating Oxidative Stress, Is Elevated in Subclinical Hypothyroidism - Xiaochun Ma; Furong Wang; Xiaowen Zhen; Lifang Zhao; Li Fang; Zhenfang Dong; Wenbin Chen; Xiaoming Zhou (International Journal of Endocrinology)
Background. gp91phox, the catalytic core of NADPH oxidase (NOX) and biomarker of NOX activation, has been recently recognized as a parameter of systemic oxidative stress in several studies. Subclinical hypothyroidism (SH) is characteristic of elevated level of serum thyroid stimulating hormone (TSH) and is frequently accompanied with cholesterolemia. In this study, the levels of serum soluble gp91phox were measured to assess the oxidative stress in patients with SH. And the relationship among gp91phox, low-density lipoprotein-C (LDL-C), and TSH was also investigated. Methods. A total of 51 subjects were enrolled and categorized into four groups: the healthy controls subjects (n = 13), controls with high level of LDL-C alone (n = 12), SH with normal level of LDL-C (n = 11), and SH with high level of LDL-C (n = 15). The related clinical and laboratory data were collected for statistical analysis. All the patients were newly diagnosed and did not take any medication. The information of lipid profile and thyroid function was extracted, and the concentrations of gp91phox were obtained with ELISA. Results. The levels of serum soluble gp91phox evidently increased in the patients with SH with a high level of LDL-C (81.52 ± 37.00 ug/mL) as compared to the healthy controls (54.98 ± 1.83ug/mL, p<0.001), controls with high level of LDL-C (61.21 ± 4.48 ug/mL, p=0.038) and SH with a normal level of LDL-C (62.82 ± 11.67ug/mL, p=0.027). Additionally, the levels of gp91phox showed a significant positive correlation with both the levels of LDL-C (r = 0.595, p<0.001) and TSH (r = 0.346, p=0.013) by the Spearman correlation analyses. The correlation remained significant even when the effect of another factor was controlled (TSH: when the effect of LDL-C was controlled, r = 0.453, p=0.001; LDL-C: when the effect of TSH was controlled, r = 0.291, p=0.040). The main effect analysis showed an independent main effect of either LDL-C (p = 0.041) or TSH (p=0.022) on gp91phox without interaction (p=0.299). Conclusions. Our work demonstrated that the levels of gp91phox, a novel biomarker for measuring the oxidative stress, were significantly elevated in the patients with SH. And LDL-C and TSH were both independent predictors of gp91phox. Abbreviations. BMI : Body mass index; TC : Total cholesterol; LDL-C : Low-density lipoprotein cholesterol; HDL-C : High-density lipoprotein cholesterol; TG : Triglyceride; FBG : Fasting blood glucose; FT3 : Free triiodothyronine; FT4 : Free thyroxine; TSH: Thyroid stimulating hormone; SBP : Systolic blood pressure; DBP : Diastolic blood pressure; SD : Standard deviation; LSD: Least significant difference.